Polytechnic student’s readiness towards project based employment - Yee, M. H.; Mohamad, N. A.; Ahmad Zubir, R. A.; Kok, B. C.; Tee, T. K. (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Project Based Employment (PBE) is the current trend in employment that is gaining momentum. The growing need for PBE has led to the need for employees with high knowledge and skills as well as good attitude. The aim of this study is to identify the readiness of polytechnic students towards PBE in two Conventional Polytechnic from the southern zone states. This study employed a survey method. A total of 361 students comprised of first, second and third year from Civil Engineering, Electrical Engineering and Mechanical Engineering courses from Politeknik Melaka and Politeknik Port Dickson were selected as study samples. The instrument of this study is a questionnaire with the alpha value .919. Data obtained were analysed using SPSS software version 21.0. Descriptive analysis in the form of mean score was used to identify the readiness of polytechnic students towards PBE. The findings show that polytechnic student`s readiness is in high level in terms of knowledge, skills and attitude towards PBE. From the knowledge aspect, polytechnic students know that PBE can provide employers with skilled and knowledgeable employees. Meanwhile, from the employability skills aspect, it shows that polytechnic students have the ability to interact well when working in groups. From the technical skills aspect, polytechnic students can complete their practical work by using the right equipment corresponding with the current PBE demands. From the attitude aspect, polytechnic students are always trying to develop themselves in the field they are involved in. In conclusion, polytechnic students are ready to face PBE in the future and they have initiative to improve their knowledge, skills and attitudes to the higher level to align with current industry demand. Overall, the results of this research have been able to help graduates and other educational institutions to improve and enhance the quality of students in line with the country's demand.